Perceived teacher support and language anxiety in Polish secondary school EFL learners - Piechurska-Kuciel, Ewa (Studies in Second Language Learning and Teaching, 2011)
The teacher’s role is vital, both in respect to achieving academic goals, and with regard to the regulation of emotional and social processes. Positive perceptions of teacher support can endorse psychological wellness, and help maintain students’ academic interests, higher academic achievement and more positive peer relationships. The teacher who shows understanding, empathy and consistency in their behavior helps students start forming an identity, which will assist them in coping with stress and anxiety directly connected with the foreign language learning process (language anxiety). The main aim of this research is to investigate the relationship between teacher support and language anxiety levels. It is speculated that teacher support functions as a buffer from the effects of negative emotions, such as language anxiety experienced in the foreign language learning process. The participants of the study were 621 secondary grammar school students whose responses to a questionnaire were the main data source. The results of the study demonstrate that students with higher levels of teacher support experience lower language anxiety levels in comparison to their peers with lower levels of teacher support. Students who have a feeling that they can count on the instructor’s help, advice, assistance, or backing manage the learning process more successfully. They evaluate their language abilities highly and receive better final grades. Nevertheless, gender and residential location do not moderate teacher support and language anxiety due to the specificity of the sample consisting of novice secondary grammar school students.